Validity and Reliability of the Persian Version of Direct Observation of Procedural Skills Tool in Audiology - Reza Alborzi; Jalil Koohpayehzadeh; Masoumeh Rouzbahani (Shahid Beheshti University of Medical Sciences, 2021)
Background and Aims: Direct Observation of Procedural Skills (DOPS) is a method for objective assessment of clinical skills by providing feedback. The present study aims to evaluate the reliability and validity of the Persian version of DOPS for the assessment of clinical skills in audiology students. Methods: In this descriptive analytical study with a cross-sectional design, participants were the students of audiology internship in the School of Rehabilitation Sciences, Iran University of Medical Sciences, Tehran, Iran. According to the panel of experts, three basic skills were selected as assessment items from among the main skills of audiology. After declaring consent, the students were assessed by a trained examiner while performing clinical skills in real clinical environment, and the results were recorded in a structured checklist. Then, students received feedback in an appropriate environment. Face, content, and construct validity and reliability of the Persian DOPS were then evaluated. Results: The content validity index of the Persian DOPS was more than 0.79, and its Content validity ratio was more than 0.42. Spearman correlation coefficient for the relationship of pure tone assessment, tinnitus assessment, and auditory brainstem response assessment with the total DOPS score were 0.785, 0.704, and 0.742, respectively indicating its acceptable construct validity (p < 0.001). Cronbach's alpha value for the reliability of the Persian DOPS was reported 0.788. Minimum and maximum values ​​of the correlation coefficient for the inter-rater reliability were 0.504 and 0.837, respectively which were significant in all tests. Students' and raters' satisfaction with the Persian DOPS was 88% and 100%, respectively ranged from satisfied to very satisfied. Conclusion: The Persian DOPS is a valid and reliable tool for the objective assessment of procedural skills in audiology.